Pollution of Siberian rivers with microplastic: the way to Arctic seas - Frank, Yuliya A.; Vorobiev, Egor D.; Kyler, O. A.; Kulinicheva, Ksenia S.; Trifonov, Andrey A.; Vorobiev, Danil S. (2021)
For the first time, a quantitative analysis of microplastics in surface waters and bottom sediments of Siberian rivers has been carried out. The average content of particles in water varied from 2.58 ± 1.87 units / m3 for a remote tributary of the Yenisei, r. Lower Tunguska, up to 51.2 ± 36.5 units / m3 for the river. Ob. Microplastic is also found in river bottom sediments. The detection of microplastics in the Ob and Yenisei confirms the possibility of the transfer of particles with river runoff to the Kara Sea.